Legal regulation of tax management in Ukraine - Oliynychuk, Oleksandra; Chaika, Iryna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2019)
The domestic and foreign experience of organization of the tax system and tax management in particular are analyzed. The various vectors of economic interests in tax management are substantiated. The structure of tax legislation is highlighted. The legal support and evolution of tax management development are considered. The disadvantages of legal support of tax management in Ukraine are outlined and ways of its improvement are formulated.